2015
DOI: 10.1002/bem.21944
|View full text |Cite
|
Sign up to set email alerts
|

Low intensity magnetic field influences short‐term memory: A study in a group of healthy students

Abstract: This study analyzes if an external magnetic stimulus (2 kHz and approximately 0.1 μT applied near frontal cortex) influences working memory, perception, binary decision, motor execution, and sustained attention in humans. A magnetic stimulus and a sham stimulus were applied to both sides of the head (frontal cortex close to temporal-parietal area) in young and healthy male test subjects (n = 65) while performing Sternberg's memory scanning task. There was a significant change in reaction time. Times recorded f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 63 publications
0
9
0
Order By: Relevance
“…Kumari, et al [35] findings suggest that exposure to a 7.5 kHz, 120 μT MF may lead to mild learning and memory impairment possibly through an inflammatory reaction in the hippocampus. From Navarro, et al [37] results, it seems that a low intensity 2 kHz exposure modifies short-term working memory, as well as perception, binary decision, motor execution, and sustained attention. Barbault, et al [38]; Capstick, et al [39] reported that cancer cell growth may be altered by very low level magnetic fields modulated at specific frequencies in humans.…”
Section: The Hyperfine Coupling Mechanism Of Biological Effects On Anmentioning
confidence: 90%
See 1 more Smart Citation
“…Kumari, et al [35] findings suggest that exposure to a 7.5 kHz, 120 μT MF may lead to mild learning and memory impairment possibly through an inflammatory reaction in the hippocampus. From Navarro, et al [37] results, it seems that a low intensity 2 kHz exposure modifies short-term working memory, as well as perception, binary decision, motor execution, and sustained attention. Barbault, et al [38]; Capstick, et al [39] reported that cancer cell growth may be altered by very low level magnetic fields modulated at specific frequencies in humans.…”
Section: The Hyperfine Coupling Mechanism Of Biological Effects On Anmentioning
confidence: 90%
“…The biological effects of extremely low-frequency (0 to 300 Hz) magnetic fields (ELF-MFs) are presented [21][22][23][24][25][26][27][28][29][30][31][32][33][34]. The biological effects of intermediate frequency (300 Hz to 100 kHz) magnetic fields(IMF-MFs)are discussed [35][36][37][38]. The biological effects of radio frequency (100 kHz to 300 GHz) magnetic fields (RF-MFs) are talked about [39][40][41][42].…”
Section: Introductionmentioning
confidence: 99%
“…Although clinical applications of magnetic fields most commonly involve high intensity fields that trigger action potentials and activate neural circuits ( Müller-Dahlhaus & Vlachos, 2013 ), therapeutic effects are also observed during low intensity magnetic stimulation ( Di Lazzaro et al, 2013 ; Rohan et al, 2014 ). For example in humans, low intensity repetitive transcranial magnetic stimulation (LI-rTMS; pulse amplitude <100 mT) is beneficial in treating depression ( Martiny, Lunde & Bech, 2010 ) and pain ( Shupak, Prato & Thomas, 2004 ) and influences memory ( Navarro, Gomez-Perretta & Montes, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…Although clinical applications of magnetic fields most commonly involve high intensity fields that trigger action potentials and activate neural circuits [Müller-Dahlhaus and Vlachos, 2013], therapeutic effects are also observed during low intensity magnetic stimulation [Di Lazzaro et al, 2013;Rohan et al, 2014]. For example in humans, low intensity repetitive transcranial magnetic stimulation (LI-rTMS; pulse amplitude <100 mT) is beneficial in treating depression [Martiny et al, 2010] and pain [Shupak et al, 2004] and influences memory [Navarro et al, 2016].…”
Section: Introductionmentioning
confidence: 99%